Analysis of Employee Work Ethic in Improving Performance in Mampotu Village, Amali District, Bone Regency - Syamsiar*, Syamsiar; Asmanurhidayani, Asmanurhidayani; Faizal, Ahmad; Illang, Nur (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Work ethic is a positive attitude or ability to work well possessed by an employee, particularly those in the Mampotu Village, Amali District, Bone Regency. This study aims to analyze the work ethic of employees in improving performance in Mampotu Village, Amali District, Bone Regency, and what factors influence the work ethic of employees in improving performance in Mampotu Village, Amali District, Bone Regency. This research is qualitative, utilizing observation, interviews, and documentation as data collection techniques. The data analysis follows an interactive analysis model. The research results regarding the work ethic of employees in improving performance in Mampotu Village, Amali District, Bone Regency reveal that the work ethic of employees in Mampotu Village, Amali District, Bone Regency is considered very good. Factors influencing the work ethic in improving performance in Mampotu Village, Amali District, Bone Regency can be assessed from several factors, namely, economic structure, religion, social, political, educational, motivational, and work discipline. Therefore, it can be concluded that the good work ethic of employees and certain factors have contributed to the improvement of performance in Mampotu Village, Amali District, Bone Regency.